The use of ’veiled language’ in Soqoṭri poetry - Morris, Miranda (Proceedings of the Seminar for Arabian Studies, 2013)
Soqoṭra is well known for its rich and unique flora and fauna, both marine and terrestrial. In 2008 it was officially declared a UNESCO World Heritage Site: ’globally important for biodiversity conservation’. The islanders who live there, however, are equally noteworthy: they speak their own unique language, Soqoṭri, and have used it to create a rich and complex oral literature. Poetry and song used to be a normal part of everyday life on the island, a natural way of communicating with others, be they human, animal, spirits of the dead, jinn, sorcerers, or the divine. The paper discusses the concept and use of ’veiled language’ in Soqoṭri oral poetry and song. Examples are given which demonstrate different levels of use of such ’veiled language’, from the readily comprehensible to the really obscure. To date, Soqoṭri poetry has been little studied, and this interesting aspect of the skill of the island’s poets has not been previously addressed.